2007
DOI: 10.1002/ar.20510
|View full text |Cite
|
Sign up to set email alerts
|

Gross anatomical study of the sympathetic cardiac nerves in the house musk shrew (Suncus murinus)

Abstract: The sympathetic cardiac nerves originating from the cervical and upper thoracic sympathetic ganglia in the house musk shrew (Suncus murinus) were examined using macroscopic and whole-mount immunohistochemical methods. Based on the results, the nerves were macroscopically classified into the following three groups: nerves innervating the cervical sympathetic ganglia mainly to the arterial porta of the heart; nerves supplying the stellate and thoracic sympathetic ganglia at the level of T2-T5 or T6 for both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…According to Kolesnikov (1935), the MG communicates with C4–5 on the left side of the chimpanzee, whereas the MG communicates with C4 on the left side of the orangutan. Eisler (1890) also found that the MG communicates with C3–4 in the gorilla (van den Broek,1908). Unfortunately, these ECNP studies in the gorilla and chimpanzee by Botar (1931a,b,1932), the orangutan by Riegele (1925–1926), and in the orangutan by Sonntag (1924) remain unclear.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to Kolesnikov (1935), the MG communicates with C4–5 on the left side of the chimpanzee, whereas the MG communicates with C4 on the left side of the orangutan. Eisler (1890) also found that the MG communicates with C3–4 in the gorilla (van den Broek,1908). Unfortunately, these ECNP studies in the gorilla and chimpanzee by Botar (1931a,b,1932), the orangutan by Riegele (1925–1926), and in the orangutan by Sonntag (1924) remain unclear.…”
Section: Discussionmentioning
confidence: 98%
“…A few ACNS studies have been conducted on the great apes. Neither side of the MG communicates with any cervical nerve in the orangutan (van den Broek,1908). According to Botar (1932), neither side of the MG communicates with any cervical nerve in the gorilla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the lower limit of TN is difficult to correctly identify because TN is quite slender and has a complicated course along the vessel, appearing irregularly throughout the posterior mediastinum. Tanaka et al (2007) described the lowest origin of TN originating from 9TG in shrew (Suncus murinus) and Fig. 1 Photographs showing the autonomic cardiac nervous system (ACNS) in humans.…”
Section: Cardiac Nerves/branchesmentioning
confidence: 99%
“…Furthermore, studies on the sympathetic nervous system have been divided into the following two types: research on the proximal part from the spinal nerves to the sympathetic ganglia (Axford 1927(Axford -1928Becker and Grunt 1957;Harman 1900;Hoffman 1957;Jamieson et al 1952;Kuntz 1946;Mitchell 1953;Pick and Sheehan 1946;White and Smithwick 1952;Wrete 1959), and research on the distal part from the sympathetic ganglia to the visceral nerves (Ellison and Williams 1962;Fukuyama 1982;Hausman 1956;Janes et al 1986;Kuntz and Morehouse 1930;Mizeres 1963;Mitchell 1953;Pick 1970). Although a few excellent anatomical studies on the ACNS have been conducted recently (Batulevicius et al 2003(Batulevicius et al , 2005Pauza et al 2000Pauza et al , 2002Saburkina et al 2010;Tanaka et al 1998Tanaka et al , 2007, numerous points remain to be clarified regarding future human applications.…”
Section: Introductionmentioning
confidence: 99%